Pengaruh Model Team Games Tournament (TGT) Berbantu Media Ubur-Ubur Terhadap Hasil Belajar Matematika Siswa Kelas lV SD - Lutfiah, Zumrotun; Marlianda, Rendi; wulandari, Resti (Universitas Batanghari Jambi, 2024)
This study applies the Team Games Tournament learning model assisted by jellyfish media in Mathematics learning.This study uses the type of Quasy Experimental Design research. The population in this study were all students of SDN 02 Timpehand the samples were two classes, namely class lVA and lVB totaling 32 students. The data collection technique was taken usingpretest and posttest sheets which were calculated and compared based on the criteria and analyzed with normality tests,homogeneity tests, and hypothesis tests through SPSS 20 at a level of 0.05. While the data collection technique was taken using atest sheet and then analyzed using normality tests, homogeneity tests, and hypothesis tests through SPSS 20 at a level of 0.05. Theresults of data analysis from the hypothesis test on the independent sample t test with a significance level of 0.05 showed theresults of sig. (2-tailed) smaller than Ha, so Ho was rejected. While the results of the test data analysis from the hypothesis test onthe independent sample t test with a significance level of 0.05 showed the results of sig. (2 tailed) smaller than a, so Ho wasrejected. Based on the results of the analysis of observation data and test data, it can be concluded that the team gamestournament learning model has a significant influence on the learning outcomes of Mathematics in grade IV of ElementarySchool